Gearbox power loss. Part I: Losses in rolling bearings. (August 2015) - Fernandes, Carlos M.C.G.; Marques, Pedro M.T.; Martins, Ramiro C.; Seabra, Jorge H.O.
Abstract: This work is devoted to the analysis, modeling and validation of gearbox power loss, considering the influence of the gears, rolling bearings and seals, the influence of the operating conditions, lubricant formulation and the lubrication method. The first part of this work a rolling bearing torque loss model is calibrated for several wind turbine gear oils and for ball and roller contacts. The results achieved clarify the importance of a rolling bearing in a gearbox power loss. In the second part of this work will be presented the same approach for gears. The final part will converge in the application of findings in two full gearboxes, a planetary and a parallel axis gearbox, both in multiplying configuration. Abstract : Highlights: Power loss in rolling bearings lubricated with wind turbine gear oils. Comparison between numerical predictions and experimental results. Adjustment of the lubricant dependent friction constants in the model.